Populism in the New Mediated Public Space. Interaction between Politics and Journalism: the Italian Peculiar Case - Rizzuto, Francesca (Populismo y propaganda: entre el presente y el pasado, 2020)
The paper will focus on the transformation of Italian political journalism and on the development of television market model in the last two decades, which brought about the success of the entertainment frame in political news. However, from the traditional advocacy journalism, Italian infotainment developed in a very peculiar direction, connected to this economic and cultural context. From the half of the 19th century, the Italian journalism was an instrument of political participation: reporters were members of a party, defended a political perspective or, which is even more dangerous, remained parallel to power. Newspapers have been used as microphones of politics, to offer visibility to leaders, without giving voice to readers. Only in the 90s the emergence of commercial television, the success of its language and formats, as well as the private TV news, made a radical change possible (Castronovo & Tranfaglia, 1994; Murialdi, 2006; Rizzuto, 2009). We can assert that an Anglo-Saxon news model, based on the watchdog ideal of neutrality and control of politicians, affirmed in a peculiar mix with the commercial perspective. For the first time in Italy, the market became important in news but with traditional elements still existing: according to Schudson (2003), in the market model, news is a product and must be sold to an audience. Nowadays Italian political journalism presents some peculiarities deriving from its parallelism to politics as well as the recent success of infotainment and the new central role of social media which are changing the traditional communication flow from leaders to voters. In two decades traditional mediation role of journalists almost disappeared: Movimento 5 Stelle is the most evident example of a new way of communicating without any form of informative mediation, which encourages populist forms of building political realty. A light use of news, focused on emotions and conflict to avoid complexity, is now more important than the traditional moral and cultural duty to be an informed citizen.